Correlation between Nurse Practice and Pre-hospital Ambulance Service Satisfaction in Bali - I Wayan Edi Sanjana; Titin Andri Wihastuti; Nurul Muslihah (Fakultas Kedokteran Universitas Brawijaya, 2022)
The pre-hospital emergency service was the first guard of nursing and treatment delivery. The pre-hospital ambulance service could be used to offer first aid to the patient or victim who experienced trauma or non-trauma with unpredictable condition. The improvement of service quality on emergency sector was required to assure that the health service was given and performed well. This research was aimed to analyze the correlation between nurse practice and pre-hospital ambulance service satisfaction in Bali. The correlative analytic research method and cross sectional approach were exerted to accomplish this research. The total sample was 271 respondents which were consisted of 144 patients and 127 nurses. The result of Spearman-rank referred p value 0.024; r 0.189 which it was indicated a significant relation between nurse practice and pre-hospital ambulance service satisfaction in Bali. The nurse practice was instituted through educational degree and training experience. The improvement of nurse practice value was in line with the pre-hospital ambulance service satisfaction value in Bali.